2011
DOI: 10.5851/kosfa.2011.31.5.668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Goldenrod (Solidago virgaurea) Leaf and Stem Powder on Physical and Sensory Characteristics of Emulsion-type Sausages

Abstract: The effects of adding goldenrod leaf (GL) and stem powder (GS) (1 and 2%) to sausage meat were evaluated for quality characteristics. The compositional properties, pH, cooking yield, instrumental color, emulsion stability, viscosity, texture, and sensory properties were investigated. Adding GL and GS increased the moisture and ash concentration in sausages. Furthermore, increasing the amount of added GL and GS helped to develop (p<0.05) cooking yield, emulsion stability, and viscosity in the meat batters. Saus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Puolanne (1999) reported that the water-binding capacity affected the content of the ingredient and the interactions of the ingredient to each other, in particular, non-meat ingredients. Similar trends in the proximate composition were observed in reducedfat sausage supplemented with brown rice fiber ( Choi et al , 2011 ); in dry fermented sausage supplemented with wheat, oat, and fruit fiber ( García et al , 2002 ); and in emulsified sausage added with goldenrod leaf and stem powder ( Choe et al ., 2011 ). Therefore, red beet powder contributed the moisture and fat content by the emulsion stability.…”
Section: Resultssupporting
confidence: 52%
“…Puolanne (1999) reported that the water-binding capacity affected the content of the ingredient and the interactions of the ingredient to each other, in particular, non-meat ingredients. Similar trends in the proximate composition were observed in reducedfat sausage supplemented with brown rice fiber ( Choi et al , 2011 ); in dry fermented sausage supplemented with wheat, oat, and fruit fiber ( García et al , 2002 ); and in emulsified sausage added with goldenrod leaf and stem powder ( Choe et al ., 2011 ). Therefore, red beet powder contributed the moisture and fat content by the emulsion stability.…”
Section: Resultssupporting
confidence: 52%
“…According to Lee and Sohn (1994) , this observation is caused by the water-binding ability of fiber. Many authors reported that the addition of dietary fiber s, such as rice bran, black rice, and isolated soy bean led to increases in cooking yield by enhancing the water-holding capacity and protein-binding ability of the meat ( Choe et al., 2011 ; Steenblock et al, 2001 ).…”
Section: Resultsmentioning
confidence: 99%
“…The viscosity of emulsified meat mince is closely related to its fat and water retaining capacity ( Choe et al, 2011 ). As depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids, saponins, caffeoylquinic acid derivatives, salicylic acid derivatives, clerodane-type diterpenes, polysaccharides, and essential oils have been reported as bioactive constituents of extracts. It has been revealed that the active substances responsible for antioxidant and anti-inflammatory activity are mainly caffeoylquinic acids and their derivatives [103][104][105][106][107][108][109][110]. Triterpenes, leiocarposide, rutin, and quercetin are also responsible for anti-inflammatory properties.…”
Section: Phytochemical Constituentsmentioning
confidence: 99%